1987
DOI: 10.1002/ajmg.1320280410
|View full text |Cite
|
Sign up to set email alerts
|

Steroid metabolic disturbances in Prader‐Willi syndrome

Abstract: We have studied steroid sulfate conjugates in serum samples from 17 children with Prader-Willi syndrome (PWS) by extraction, enzymatic hydrolysis and chromatography of the hydrolysed, free steroids. The chromatograms in patients with PWS can be divided into 2 classes. Ten (4 with the deletion on chromosome 15 and 6 without) of 17 had a normal pattern with dehydroepiandrosterone (DHEA) as the only steroid detected. However, 7 out of 17 (3 with the deletion and 4 without) had a very different pattern. The chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 9 publications
2
2
0
Order By: Relevance
“…STAR plays a key role in the acute regulation of steroid hormone synthesis by enhancing the conversion of cholesterol into pregnenolone. This observation is supported by steroid metabolite disturbances previously reported in PWS [Chasalow et al, 1987]. Specifically, Chasalow et al 1987 reported that PWS subjects secreted large amounts of sulfo‐conjugates, including dehydroepiandrosterone (DHEA) and mono‐ and dihydroxypregnenolone.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…STAR plays a key role in the acute regulation of steroid hormone synthesis by enhancing the conversion of cholesterol into pregnenolone. This observation is supported by steroid metabolite disturbances previously reported in PWS [Chasalow et al, 1987]. Specifically, Chasalow et al 1987 reported that PWS subjects secreted large amounts of sulfo‐conjugates, including dehydroepiandrosterone (DHEA) and mono‐ and dihydroxypregnenolone.…”
Section: Discussionsupporting
confidence: 55%
“…This observation is supported by steroid metabolite disturbances previously reported in PWS [Chasalow et al, 1987]. Specifically, Chasalow et al 1987 reported that PWS subjects secreted large amounts of sulfo‐conjugates, including dehydroepiandrosterone (DHEA) and mono‐ and dihydroxypregnenolone. In addition, pregnane steroids can potently and specifically enhance GABA A receptor function acting as remote endocrine messengers [Lambert et al, 2003; Belelli and Lambert, 2005].…”
Section: Discussionsupporting
confidence: 55%
“…To date, growth hormone (GH) insufficiency and hypogonadism are well described, and the gonadal development at puberty is typically delayed or incomplete. Surprisingly, in this context, premature adrenarche may be observed in children affected by PWS [11, 12, 13, 14, 15], although the insulin [16]and IGF-I [17]levels are below the normal average due to insufficient GH secretion [18]. The issue of accelerated adrenal development against a background of hypothalamic-pituitary insufficiency in PWS has not yet been explained.…”
Section: Introductionmentioning
confidence: 99%
“…It is probable that the observed increase in DHEA-S may be similar to increased DHEA-S in pubarche or precocious puberty. On the other hand, Chasalow et al(1987) suggested that Prader-Willi syndrome may have the common clinical manifestations of a variety of different defects in the sulfoconjugate metabolic pathway. Adrenal suppression by dex.…”
mentioning
confidence: 99%